Funkcje wsi. Ewolucja koncepcji i współczesne wyzwania badawcze = Functions of rural areas. Evolution of concepts and contemporary research challenges - Wójcik, Marcin. Autor (IGiPZ PAN, 2019)
Functionalism in the Polish geographical studies has been the basic research approach within the broadly understood rural geography. Implementation of this paradigm for over 30 years (until the end of the 1980s) in numerous geographical research centers has consolidated a model primarily based on statistical sources and their development employing quantitative methods. At present, scientists face challenges concerning a holistic view on the cultural change taking place in Poland’s rural areas and its geographical description involving qualitative research methods. The aim of this paper is to indicate the origin of approaches addressing the issue of rural areas’ functions, their evolution and gradual replacement or supplementation with new trends, interpretation of which requires employing experience gained by social sciences. The final part of the paper includes a proposal of redirecting research towards a new look at changes occurring in Poland’s rural areas. Contemporary processes of social diversification could find a perfect interpretation of the rural environment in the cultural concept. Some key research tasks included in the solution to this problem are: • defining the functions of settlement units within area’s structure and changes in cultural landscape, along with identification of their natural and socio-economic conditions; • determining the social structure and its transformation trends in rural settlements; • linking physiognomic features of development and utilization of settlement plots and social characteristics of their inhabitants; • determining the spatial and temporal activity of rural population; • determining the existing social relations between village’s inhabitants (forms of cooperation and possible conflicts); • identifying rationale behind social behavior, including inhabitants’ participation in the formation and functioning of local government.
24 cm
Keywords: rural area; functions; theoretical and methodological transformation; Poland